Differential in vitro kinetics of drug resistance mutation acquisition in HIV-1 RT of subtypes B and C. - Rodrigo D Cunha (Public Library of Science (PLoS), 2012)
Background HIV-1 subtype B is the most prevalent in developed countries and, consequently, it has been extensively studied. On the other hand, subtype C is the most prevalent worldwide and therefore is a reasonable target for future studies. Here we evaluate the acquisition of resistance and the viability of HIV-1 subtype B and C RT clones from different isolates that were subjected to in vitro selection pressure with zidovudine (ZDV) and lamivudine (3TC). Methods/principal findings MT4 cells were infected with chimeric virus pseudotyped with RT from subtype B and C clones, which were previously subjected to serial passage with increasing concentrations of ZDV and 3TC. The samples collected after each passage were analyzed for the presence of resistance mutations and VL. No differences were found between subtypes B and C in viral load and resistance mutations when these viruses were selected with 3TC. However, the route of mutations and the time to rebound of subtype B and C virus were different when subjected to ZDV treatment. In order to confirm the role of the mutations detected, other clones were generated and subjected to in vitro selection. RT subtype B virus isolates tended to acquire different ZDV resistance mutations (Q151M and D67N or T215Y, D67D/N and F214L) compared to subtype C (D67N, K70R, T215I or T215F). Conclusions/significance This study suggests that different subtypes have a tendency to react differently to antiretroviral drug selection in vitro. Consequently, the acquisition of resistance in patients undergoing antiretroviral therapy can be dependent on the subtypes composing the viral population.